(untitled) (Journal of the College of Basic Education, 2025)
The poetic image is a meticulously woven construct, shaped by the poet’s skill and unique creativity. It serves as the external framework for the structure of poetry, encompassing the processes of depiction and verbal composition. A poetic image is akin to an artistic painting, brought to life through the interplay of imaginative and sensory meanings, supported by additional resources that enhance the aesthetic structure of the poetic text. Human senses, with their active role, are among the most significant sources of artistic imagery, complemented by the tools of expression provided by imagination. By employing these senses, the poet expands the perceptions of the image, imparting depth and tangibility to the poetic text. This makes the senses a fundamental component in shaping poetic imagery. Amid this extensive use of imagery, the poetry of Muwaffaq al-Din al-Mada’ini (d. 656 AH) stands out. He utilized sensory perceptions to infuse his poetry with both objective and aesthetic meanings, crafting images that evoke life, sound, and sensation in harmony with his poetic experience